Urgensi Revitalisasi Butir-Butir Pancasila Dalam Kehidupan Masyarakat Untuk Menangani Lunturnya Karakter Bangsa Indonesia Di Era Globalisasi - Habibah, Siti Maizul (Jurnal Pancasila dan Bela Negara, 2024)
The adverse effects of globalization can convert all aspects of people's lives. The negative effects of waves in the  era of globalization are so great that they are unstoppable, reflected in the attitude of a non-selective society  towards foreign cultures, so it is feared that it will gradually affect the character of the nation and pose a threat  to the integrity and resilience of Indonesia's national identity because it can end up eating away and softening  the nation's identity. Therefore, it is necessary to revive the role of Pancasila as a foundation for ethos,  ideological, and identity defense mechanisms to deal with the influence of globalization. By collecting a variety  of references from primary and secondary sources, including journals, books, articles, research papers, and a  wide variety of materials from various websites, the study uses a literature study methodology. The literature  review is carried out to support the issues under study and become the basis for various arguments about the  nature of the nation as a national identity as well as efforts to preserve and overcome the difficulties of national  identity in the era of globalization. This study aims to examine the urgency of revitalization in the actualization  of Pancasila items. Based on the results of the research, it is hoped that the public can understand the  importance of revitalizing the grains of Pancasila as a reflection of life in the face of the fading of the nation's  character in the era of globalization.